A Comprehensive Review of Cybersecurity Measures in the IoT Era - Ezatullah Ahmady; Abdul Rahman Mojadadi; Musawer Hakimi (Journal of Social Science Utilizing Technology, 2024)
Background. This research presents a comprehensive review of cybersecurity measures in the Internet of Things (IoT) era. The primary focus is on elucidating the evolving landscape of IoT cybersecurity, with specific attention to the integration of Artificial Intelligence (AI), machine learning, and risk management. The study aims to identify key advancements, challenges, and opportunities in securing interconnected devices, offering valuable insights for researchers, policymakers, and industry professionals. Purpose. Employing a hybrid methodological design that combines elements from narrative synthesis and heuristic analysis, this study utilizes purposive and snowball sampling techniques to select diverse and pertinent sources. The integration of semantic analysis, leveraging natural language processing algorithms, enriches data interpretation. Collaborative intelligence from cybersecurity, machine learning, and IoT experts enhances the study's perspective. A proprietary algorithm, incorporating machine learning principles, enhances data collection efficiency. Method. The synthesis reveals a dynamic landscape marked by the symbiotic relationship between AI and IoT, fortifying defenses against cyber threats. Machine learning emerges as a potent ally, providing robust solutions for threat detection. The study identifies challenges in implementing cybersecurity measures in the IoT landscape, including data privacy, scalability, and regulatory compliance. Results. In conclusion, the review emphasizes the need for proactive and adaptive security strategies in the IoT era, highlighting the role of AI and collaborative interdisciplinary approaches. The study provides a roadmap for future research, policy formulation, and industry practices to fortify the security posture of the IoT ecosystem. Conclusion. This study has comprehensive review of IoT cybersecurity illuminates a dynamic landscape marked by the symbiotic relationship between Artificial Intelligence (AI) and the Internet of Things (IoT). The integration of AI signifies a paradigm shift towards proactive and adaptive security strategies, enhancing the resilience of IoT ecosystems against evolving cyber threats.